The Influence Of Social Interaction On Tiktok Shop Purchasing Decisions - Sumantyo, Franciscus Dwikotjo Sri; Hussaen, Saddam; Setyawan, Aditya Chandra; Hamdiah, Hamdiah; Yakin, Rahmat Aji Nur (Interdisciplinary Explorations in Research Journal, 2026)
This study aims to analyze the influence of social interaction on purchasing decisions on the TikTok Shop platform. In the era of social commerce, the shift from transactional to interactional shopping experiences has redefined consumer behavior. Through the lens of Social Cognitive Theory and the concept of "shoppertainment," this research investigates how real-time engagement, peer recommendations, and influencer interactions shape consumer trust and urgency. The findings suggest that social interaction manifested through live streaming comments, likes, and shares acts as a catalyst that significantly reduces the consumer's decision-making journey. This abstract highlights the importance of two-way communication in modern digital marketing.